Patient selection criteria and midterm clinical outcome for MitraClip therapy in patients with severe mitral regurgitation and severe congestive heart failure. (July 2013) - Neuss, Michael; Schau, Thomas; Schoepp, Maren; Seifert, Martin; Hölschermann, Frank; Meyhöfer, Jürgen; Butter, Christian
<x xml:space="preserve">Abstract</x> Aims The implantation of a MitraClip (MC) is a new treatment modality for severe mitral regurgitation (MR) in patients whose condition is inoperable or who are at high conventional operative risk. This study reports the follow‐up data of patients implanted with an MC in our heart centre to find selection criteria for this procedure in patients with severe congestive heart failure. Methods and results This study included 163 implantation procedures in 157 patients between March 2009 and November 2012. The severe MR was caused by functional or organic valve disease. The patients had no surgical treatment option or dramatically increased surgical operative risk due to reduced LVEF or concomitant diseases. Three (2%) implantation procedures were unsuccessful. Eleven (7%) patients died during the first 30 days after MC implantation, and 9 (6%) additional patients died during the first 6 months, both groups mainly due to severe, therapy‐resistant end‐stage heart failure. The 111 patients who were followed up showed significant improvement in NT‐proBNP, LVEF, NYHA class, 6 min walk test, and quality of life. Ten (6%) patients needed conventional heart surgery despite high operative risk due to persistent symptomatic MR after MC implantation. Conclusion The interventional implantation of an MC is a new treatment for severe MR with acceptable periprocedural risk and results in clinical improvement in the majority. Patients with end‐stage heart failure and an NT‐proBNP value >10 000 pg/mL have a high mortality despite MC implantation, and their treatment should be based on a very individualized decision. Based on this experience, a clinical algorithm for patient selection is proposed.